Promoting Inquiry Based Science Education for children 3-11 years old in Europe: The European project PriSciNet - Καλαϊτζιδάκη Μαριάννα (Education Sciences, 2017)
In this paper we present our experience from participating in PriSciNet (2011 to 2014), an fp7-funded project of 15 partners that had the goal of promoting inquiry-based science education (IBSE) in Europe for children 3-11 years through the development of educational material and the training of pre-school and primary school teachers. Forty five activities were developed, 15 for each age group of 3-5, 6-8, 9-11years, with information for the teacher and worksheets for the students that can be implemented with everyday materials in regular classes. The Department of Primary Education of the University of Crete organized 1 international and 4 national training seminars, the evaluation of which revealed an overall positive experience for the participants, their need for further training and concerns as to whether IBSE fits within the Greek educational system. Pilot testing of activities revealed challenges and opportunities similar to those reported previously in the literature. The 45 activities have been translated in 15 languages, Greek included, to maximize their dissemination in Europe, and are available to be downloaded and used.